Metal-based polymer nanoparticle antibacterial agent as well as preparation method and application thereof

By combining triphenylphosphine modified metal-based polymer nanoparticles prepared with intramolecular crosslinking on the wound, forming a composite doping antibacterial dressing, the nanomaterials with slow sterilization in the prior art is solved. Problem, rapid sterilization and wound healing have been achieved, and wound healing efficiency and tissue repair ability have been improved.

CN119144005AActive Publication Date: 2024-12-17HARBIN INST OF TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411282517.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-17
Estimated Expiration
2044-09-13

AI Technical Summary

Technical Problem

Existing nanomaterials have slow sterilization in wound care, and the sterilization effect is not ideal, and it is difficult to effectively promote wound healing.

Method used

Intramolecular crosslinking method is used to prepare triphenylphosphine modified metal-based polymer nanoparticles with core-shell structures and combine them with polyether thiourea dressing to form a composite doping antibacterial with bacterial targeting and photothermal effect. Wound dressing.

Benefits of technology

It achieves rapid and effective bacterial killing and wound healing, improves wound healing efficiency and tissue repair ability, and the dressing has good mechanical strength and self-healing performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005042101390000011
    Figure HDA0005042101390000011
  • Figure HDA0005042101390000012
    Figure HDA0005042101390000012
  • Figure HDA0005042101390000021
    Figure HDA0005042101390000021
Patent Text Reader

Abstract

The invention discloses a metal-based polymer nanoparticle antibacterial agent and a preparation method and application thereof.The preparation method comprises the steps that polymer polypeptide is dissolved in a polar solvent, metal salt or an inorganic metal complex is added under stirring, the temperature is increased to 25-160 DEG C, a reaction is conducted for 2-24 h, a pyrolytic reaction continues after the reaction is conducted, the pyrolytic reaction temperature is 60-160 DEG C, the pyrolytic reaction time is 1-18 h, and the metal-based polymer nanoparticle antibacterial agent is obtained. And after the reaction is finished, collecting a product, cleaning and drying to obtain the metal-based polymer nanoparticle antibacterial agent. According to the invention, the inorganic-organic polymer hybridized triphenylphosphine modified metal-based polymer nanoparticles with the particle size of less than 10nm are synthesized, and the inorganic-organic hybridization stability is good. The prepared metal-based polymer nanoparticles have bacterial targeting property and can be gathered at infected parts, so that the photo-thermal effect is concentrated, and the nanoparticles are prevented from generating excessive heat to damage healthy cell tissues. The prepared antibacterial wound dressing has good stretchability and self-repairing performance, the healing efficiency of infected wounds can be further improved, and wound healing and skin tissue reconstruction are promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of antibacterial agents, and specifically relates to a metal-based polymer nanoparticle antibacterial agent and a preparation method and application thereof. Background Art

[0002] As the first line of defense of the human body, the skin is one of the main organs of the human body and has many important functions such as protection, absorption, regulation, perception and secretion. When the skin is damaged, it is very susceptible to bacterial infection, causing inflammatory reactions and reducing the patient's quality of life. Therefore, timely and effective treatment is crucial for wound healing. In addition, the moist environment on the wound surface also facilitates bacterial reproduction and accelerates cross-infection in the ward. Nanomaterials have unique advantages in wound care, such as high reactivity, large specific surface area, and the ability to control their conductivity and penetration depth by changing the size and shape of nanomaterials. However, the bactericidal effect of nanomaterials in the prior art is slow and the bactericidal effect is not ideal. Summary of the invention

[0003] In order to solve the above problems existing in the prior art, the present invention proposes a modified polyetherthiourea antibacterial wound dressing and a preparation method and application thereof.

[0004] The present invention firstly discloses a method for preparing a metal-based polymer nanoparticle antibacterial agent, which comprises the following steps: dissolving a polymer polypeptide in a polar solvent, adding a metal salt or an inorganic metal complex under stirring, heating to 25-160° C. for reaction for 2-24 hours, continuing a pyrolysis reaction after the reaction, wherein the pyrolysis reaction temperature is 60-160° C. for 1-18 hours, collecting the product after the reaction, washing and drying to obtain the metal-based polymer nanoparticle antibacterial agent.

[0005] Furthermore, the obtained metal-based polymer nanoparticle antibacterial agent is modified using a modifier.

[0006] Furthermore, the modifier is triphenylphosphine.

[0007] Furthermore, the triphenylphosphine modifier is selected from one or more of the following: n-pentyltriphenylphosphonium bromide, methyltriphenylphosphonium bromide, ethyltriphenylphosphonium bromide, n-heptyltriphenylphosphonium bromide, benzyltriphenylphosphonium bromide or (3-carboxypropyl)triphenylphosphonium bromide.

[0008] Furthermore, when the modifier is triphenylphosphine, the steps are: activating the triphenylphosphine modifier to obtain an activated triphenylphosphine solution, adding the activated triphenylphosphine solution dropwise to the metal-based polymer nanoparticle / water dispersion, stirring at room temperature in the dark until the reaction is complete, dialyzing the product solution to remove the raw materials that have not participated in the reaction, collecting the product, and washing and drying to obtain triphenylphosphine-modified metal-based polymer nanoparticles.

[0009] Furthermore, the polymer polypeptide is made of amino acids containing substituents, the amino acids are selected from one or more of the following: alanine, glutamic acid, glycine, leucine or valine, and the substituents are selected from one or more of the following: pyridyl, imidazole, carbazolyl, pyrrolyl or alkynyl.

[0010] The polymer polypeptide contains a segment of a polyethylene glycol modifier, and the polyethylene glycol modifier is selected from one or more of the following: methoxy polyethylene glycol amine, carboxyl polyethylene glycol amine or amino-terminated polyethylene glycol, and has a molecular weight of 1000, 2000, 5000 or 10000.

[0011] The degree of polymerization of the polymer polypeptide is 50-1000, preferably 50-100.

[0012] Furthermore, the metal salt is selected from one or more of the following: ferric chloride, ferrous chloride, ferric sulfate, ferrous sulfate, ferrous nitrate, ferrous carbonate or ammonium ferrous sulfate, and the inorganic metal complex is selected from one or more of the following: Fe(CO)5, Co2(CO)8, Ni(CO)4, V(CO)6, Mo(CO)6, W(CO)6, Ru(CO)5 or Mn2(CO) 10 .

[0013] Furthermore, the polar solvent is selected from one or more of the following: dimethyl sulfoxide, N,N-dimethylformamide, acetone, dioxane, tetrahydrofuran, methyl ethyl ketone, methanol, n-butanol, ether, chloroform, N-methylpyrrolidone or o-dichlorobenzene.

[0014] The particles prepared according to the above method are of core-shell structure, wherein the core is a metal oxide particle and the shell is a polymer polypeptide. Optionally, there is a modified chain.

[0015] The above-mentioned metal-based polymer nanoparticle antibacterial agent is used by adding 0.1 to 0.3 parts by weight of the metal-based polymer nanoparticle antibacterial agent and 0 to 0.001 parts by weight of the cationic antibacterial agent to 100 parts by weight of the polyether thiourea dressing precursor, and then transferring the mixture into a mold after mechanical stirring to obtain an antibacterial dressing.

[0016] Furthermore, the cationic antibacterial agent is selected from one or more of the following: dodecyltrimethylammonium chloride, dodecyldimethylbenzylammonium chloride, dodecyldimethylbenzylammonium bromide, tetradecyldimethylbenzylammonium chloride, hexadecylpyridinium bromide, polyethyleneimine or hexadecyltrimethylammonium bromide.

[0017] Compared with the prior art, the present invention has the following advantages and significant improvements:

[0018] (1) The significant advantage of the present invention is that it uses an intramolecular cross-linking method to in situ synthesize inorganic-organic polymer hybrid triphenylphosphine-modified metal-based polymer nanoparticles with a particle size of less than 10 nm. The hybrid nanoparticles have atomic-level mixing and can accurately control the composition. In addition, the nanoparticle core is formed while the polypeptide chain wraps around to form the shell. The two proceed simultaneously, and the inorganic-organic hybrid has good stability.

[0019] (2) The metal-based polymer nanoparticles prepared by the present invention have bacteria targeting properties and can gather at the infection site, thereby concentrating the photothermal effect and preventing the nanoparticles from generating excessive heat to damage healthy cell tissues. They have excellent wound healing effects and tissue repair capabilities.

[0020] (3) The composite doped polyetherthiourea antibacterial wound dressing with high mechanical strength and self-healing performance prepared by the present invention has good stretchability (about 200%) and self-healing performance, which solves the problem of the single function of nanoparticles in treating wound infections, and can further improve the healing efficiency of infected wounds and promote wound healing and skin tissue reconstruction. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is the XPS fine spectrum of Example 1;

[0022] Figure 2 This is the XPS fine spectrum of Example 3;

[0023] Figure 3 The morphology of the polyether thiourea dressing is characterized, (a) is a surface photo of the dressing (from left to right: Comparative Examples 1-3, Example 6); (b) is a side photo of the dressing of Comparative Example 1; (c) is a SEM image of Comparative Example 3; (d) is a SEM image of Example 6;

[0024] Figure 4 1 are stress-strain curves of Example 4, Example 6 and Comparative Example 1;

[0025] Figure 5 The self-repairing photos of the antibacterial dressings of Comparative Example 1 and Example 6;

[0026] Figure 6 Under near-infrared light (0.75W / cm 2 ) Photothermal properties of composite doped polyetherthiourea antibacterial dressings (Examples 4 to 8);

[0027] Figure 7 The wound areas of different groups of wounds infected with Staphylococcus aureus;

[0028] Figure 8 HE staining microscopy of tissues in different groups of rats on day 9. DETAILED DESCRIPTION

[0029] The technical solution of the present invention is further described below in conjunction with the embodiments, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.

[0030] The present invention first discloses a method for preparing a metal-based polymer nanoparticle antibacterial agent, comprising the steps of: dissolving a polymer polypeptide in a polar solvent, adding metal salts or inorganic metal complexes in sequence under stirring, heating to 25-160° C. for reaction for 2-24 hours, continuing pyrolysis reaction after the reaction, wherein the pyrolysis reaction temperature is 60-160° C. for 1-18 hours, collecting the product after the reaction, washing and drying to obtain the metal-based polymer nanoparticle antibacterial agent. Optionally, a modifier is used to modify the obtained metal-based polymer nanoparticle antibacterial agent. The modifier is triphenylphosphine. The triphenylphosphine modifier is selected from one or more of the following: n-pentyl triphenyl phosphonium bromide, methyl triphenyl phosphonium bromide, ethyl triphenyl phosphonium bromide, n-heptyl triphenyl phosphonium bromide, benzyl triphenyl phosphonium bromide or (3-carboxypropyl) triphenyl phosphonium bromide.

[0031] The polymer polypeptide is made of amino acids containing substituents, the amino acids are selected from one or more of the following: alanine, glutamic acid, glycine, leucine or valine, and the substituents are selected from one or more of the following: pyridyl, imidazole, carbazole, pyrrolyl or alkynyl. The polymer polypeptide contains a segment of a polyethylene glycol modifier, the polyethylene glycol modifier is selected from one or more of the following: methoxy polyethylene glycol amine, carboxyl polyethylene glycol amine or amino-terminated polyethylene glycol, and the molecular weight is 1000, 2000, 5000 or 10000. The degree of polymerization of the polymer polypeptide is 50 to 1000, preferably 50 to 100.

[0032] The metal salt is selected from one or more of the following: ferric chloride, ferrous chloride, ferric sulfate, ferrous sulfate, ferrous nitrate, ferrous carbonate or ammonium ferrous sulfate; the inorganic metal complex is selected from one or more of the following: Fe(CO)5, Co2(CO)8, Ni(CO)4, V(CO)6, Mo(CO)6, W(CO)6, Ru(CO)5 or Mn2(CO) 10 .

[0033] The polar solvent is selected from one or more of the following: dimethyl sulfoxide, N,N-dimethylformamide, acetone, dioxane, tetrahydrofuran, methyl ethyl ketone, methanol, n-butanol, ether, chloroform, N-methylpyrrolidone or o-dichlorobenzene.

[0034] When the modifier is triphenylphosphine, the steps are as follows: activating the triphenylphosphine modifier to obtain an activated triphenylphosphine solution, adding the activated triphenylphosphine solution dropwise into the metal-based polymer nanoparticle / water dispersion, stirring at room temperature in the dark for complete reaction, dialyzing the product solution to remove the raw materials that have not participated in the reaction, collecting the product, washing and drying to obtain the triphenylphosphine-modified metal-based polymer nanoparticles.

[0035] The particles prepared according to the above method are of core-shell structure, wherein the core is a metal oxide particle and the shell is a polymer polypeptide. Optionally, there is a modified chain.

[0036] The application of the above-mentioned metal-based polymer nanoparticle antibacterial agent is specifically to add 0.1 to 0.3 parts by weight of the metal-based polymer nanoparticle antibacterial agent and 0 to 0.001 parts by weight of the cationic antibacterial agent to 100 parts by weight of the polyether thiourea dressing precursor, and then transfer it to a mold after mechanical stirring to obtain an antibacterial dressing.

[0037] The cationic antibacterial agent is selected from one or more of the following: dodecyltrimethylammonium chloride, dodecyldimethylbenzylammonium chloride, dodecyldimethylbenzylammonium bromide, tetradecyldimethylbenzylammonium chloride, hexadecylpyridinium bromide, polyethyleneimine or hexadecyltrimethylammonium bromide.

[0038] Embodiment 1:

[0039] 60 mg of alkynyl-containing glycine polypeptide was dissolved in 60 mL of N,N-dimethylformamide, and 0.72 g of FeCl3·6H2O and 0.48 g of FeCl2·4H2O were added in sequence under stirring. The temperature was raised to 85°C for reaction for 2 h. After the reaction, the pyrolysis reaction was continued for 5 h at a temperature of 85°C. After the reaction, the product was collected, washed and dried to obtain an iron-based polymer nanoparticle antibacterial agent.

[0040] Embodiment 2:

[0041] The iron-based polymer nanoparticle antibacterial agent obtained in Example 1 was modified. The specific operation was as follows: 11.20 mg of triphenylphosphine modifier was activated to obtain 2 mL of activated triphenylphosphine solution, which was added dropwise to 30 mL of iron-based polymer nanoparticle / water dispersion, stirred at room temperature in the dark until the reaction was complete, the product solution was dialyzed to remove the raw materials that did not participate in the reaction, the product was collected, washed three times, and dried to obtain triphenylphosphine-modified iron-based polymer nanoparticles.

[0042] Embodiment 3:

[0043] 40 mg of alkynyl-containing glycine polypeptide was dissolved in 7 mL of o-dichlorobenzene, and 110 mg of octacarbonyl cobalt was added under stirring. After stirring at 25 °C for 18 h, the temperature was raised to 120 °C for pyrolysis for 16 h. After the reaction was completed, the product was collected, washed and dried to obtain a cobalt-based polymer nanoparticle antibacterial agent.

[0044] Embodiment 4:

[0045] Preparation of modified polyetherthiourea wound dressing: Add cationic antibacterial agent polyethyleneimine and triphenylphosphine-modified iron-based polymer nanoparticles prepared in Example 2 to the polyetherthiourea wound dressing precursor, transfer to a mold after mechanical stirring, and vacuum dry at above 80°C to obtain a modified polyetherthiourea antibacterial dressing. The mass ratio of triphenylphosphine-modified iron-based polymer nanoparticles, cationic antibacterial agent, and polyetherthiourea wound dressing precursor is 0.1:0.001:100.

[0046] Embodiment 5:

[0047] The mass ratio of triphenylphosphine-modified iron-based polymer nanoparticles, cationic antimicrobial agent, and polyetherthiourea wound dressing precursor is 0.15:0.001:100. The remaining steps are the same as those in Example 4.

[0048] Embodiment 6:

[0049] The mass ratio of triphenylphosphine-modified iron-based polymer nanoparticles, cationic antimicrobial agent, and polyetherthiourea wound dressing precursor is 0.2:0.001:100. The remaining steps are the same as those in Example 4.

[0050] Embodiment 7:

[0051] The mass ratio of triphenylphosphine-modified iron-based polymer nanoparticles, cationic antimicrobial agent, and polyetherthiourea wound dressing precursor is 0.25:0.001:100. The remaining steps are the same as those in Example 4.

[0052] Embodiment 8:

[0053] The mass ratio of triphenylphosphine-modified iron-based polymer nanoparticles, cationic antimicrobial agent, and polyetherthiourea wound dressing precursor is 0.3:0.001:100. The remaining steps are the same as those in Example 4.

[0054] Embodiment 9:

[0055] The mass ratio of triphenylphosphine-modified iron-based polymer nanoparticles, cationic antimicrobial agent, and polyetherthiourea wound dressing precursor is 0.1:0:100. The remaining steps are the same as those in Example 4.

[0056] Comparative Example 1:

[0057] The comparative example only contains the polyetherthiourea wound dressing precursor, and no cationic antimicrobial agent and iron-based polymer nanoparticles are added. The remaining steps are the same as those in Example 4.

[0058] Comparative Example 2:

[0059] The components of this comparative example are: cationic antibacterial agent hexadecyltrimethylammonium bromide is added to the polyetherthiourea wound dressing precursor, and the mass ratio of the polyetherthiourea wound dressing precursor to the cationic antibacterial agent is 100:0.001. The remaining steps are the same as those of Example 4.

[0060] Comparative Example 3:

[0061] The components of this comparative example are: cationic antibacterial agent polyethyleneimine is added to the polyetherthiourea wound dressing precursor, and the mass ratio of the polyetherthiourea wound dressing precursor to the cationic antibacterial agent is 100:0.001. The remaining steps are the same as those of Example 4.

[0062] Testing and characterization analysis:

[0063] In order to determine the chemical valence state of the iron element inside the iron-based polymer nanoparticles of Example 1, XPS test was performed on them. After fitting and peak separation using XPS Peak software, as shown in FIG. Figure 1 The XPS spectrum of Fe 2p3 / 2 shows four peaks at 709.5, 711.0 and 712.8 eV. The peaks at 711.0 eV and 712.8 eV correspond to the oxygen-bonded Fe 3+ (Fe(III)-O). The peak at 709.5 eV can be attributed to the oxygen-bonded Fe 2+ (Fe(Ⅱ)-O).

[0064] In order to determine the chemical valence state of the iron element inside the cobalt-based polymer nanoparticles of Example 3, XPS test was performed on them. After fitting and peak separation using XPS Peak software, as shown in FIG. Figure 2 The XPS spectrum of Co 2p3 / 2 shows that it can be divided into four peaks at 783.7eV, 782.0eV, 780.6eV and 779.1eV, corresponding to Co-C, Co 2+ ,Co 3+ And Co. This indicates that the pyrolysis products contain a small amount of cobalt oxide in addition to elemental cobalt.

[0065] By controlling the amount of doped iron-based polymer nanoparticles and PEI, a series of composite doped PETU dressings were prepared, and their morphological characteristics are as follows: Figure 3 As shown, from left to right are: Comparative Examples 1-3, Example 6. Figure 3(a, b) It can be seen that the PETU dressing has a diameter of about 1.5 cm, a thickness of about 1 mm, and an orange-yellow color. When 0.001% CTAB or PEI is added, the color of the dressing does not change substantially, but when iron-based polymer nanoparticles are added, the color of the dressing turns dark brown. Figure 3 (c) and 3(d) are SEM photos of comparative example 3 and example 6, respectively. It can be seen from the figures that the surfaces of the PETU dressing of comparative example 3 with single PEI doping and the composite doped PETU dressing of example 6 are both relatively smooth. The raised parts of the surface are due to the rapid increase in molecular weight due to high-temperature cross-linking during the preparation process, which leads to a rapid increase in viscosity and the formation of pores when the solvent evaporates.

[0066] When wound dressings are used, they are required to have good mechanical properties. Therefore, a universal testing machine was used to stretch Comparative Example 3, Example 4, and Example 6 at a fixed speed of 10 mm / min at room temperature to verify their mechanical properties. Figure 4 As shown in the figure, it can be seen that the maximum tensile stress of comparative example 3 is about 0.3MPa and the maximum strain is about 200%, indicating that it has good tensile properties. And as the doping amount of iron-based polymer nanoparticles increases, the tensile strength and elongation at break of the PETU dressing decrease, but it can still meet the application requirements of wound dressings.

[0067] Furthermore, the self-healing properties of the antibacterial dressing were tested, such as Figure 5 The dressing was cut in half from the middle, and then the gaps were merged together. After about 30 seconds, it was stretched to both sides. It can be clearly seen that the dressing has obvious repair marks, indicating that the prepared polyether thiourea dressing has good self-healing properties regardless of whether it is loaded with iron-based polymer nanoparticles.

[0068] In order to study the photothermal performance of the composite doped PETU antibacterial dressing in NIR-Ⅱ, the present invention first investigated the 0.75W / cm 2 The photothermal heating capacity of PETU antibacterial dressings with different loading amounts of iron-based polymer nanoparticles (i.e., Examples 4 to 8) under different power levels is shown in the following figure. Figure 6 As shown. Figure 6 It can be seen that the PETU antibacterial dressing loaded with iron-based polymer nanoparticles has a rapid and strong temperature-raising ability, and the temperature-raising effect is more significant with the increase of concentration. Under 1064nm near-infrared laser irradiation, the temperature of different composite doped PETU antibacterial dressings can be increased from about 29.4℃ to 50.0, 53.4, 57.7, 60.3 and 61.7℃ (in order from small to large load) within 10min, indicating that the PETU antibacterial dressing loaded with iron-based polymer nanoparticles has obvious photothermal temperature-raising ability. 50℃ is the critical value for bacterial death, so PETU-PEI-0.001%-NPs-0.2% antibacterial dressing was selected for subsequent wound treatment.

[0069] Antimicrobial therapy in a rat skin Staphylococcus aureus infection model

[0070] In order to observe the wound treatment of rats, the infected rats were randomly divided into 4 groups for wound antibacterial experiments, which are respectively Examples 10 to 13. The purchased SD rats were raised under a constant temperature and humidity, 12h light / 12h dark environment for 7 days and then the experiment was started. The rats were anesthetized with a gas anesthesia machine and then anesthetized by intraperitoneal injection of sodium barbital (30 mg / kg). The hair on the back was shaved and disinfected, and a full dermal layer loss wound (1.5 cm in diameter) was created on the back of each rat. A solution containing Staphylococcus aureus (2×10 8 CFU / mL) of bacterial suspension was evenly applied and infected for 30 minutes. The drug was applied once every other day for a total of three days. The wound healing of different treatment groups was recorded every day. The wound area was calculated using Image J. The rats were euthanized after 9 days, and the relevant wound tissues were collected. The wound tissues were fixed and encapsulated in paraffin, and the appropriate size was controlled for sectioning. After sectioning, hematoxylin and eosin staining was performed and observed under a microscope.

[0071] Embodiment 10:

[0072] This group was administered with 100 μL of PBS solution.

[0073] Embodiment 11:

[0074] The iron-based polymer nanoparticles prepared in Example 1 were dispersed in PBS solution at a ratio of 350 μg / mL. Rats were irradiated with 1064 nm NIR laser for 10 min each time (0.75 W / cm 2 ). Then use 100 μL of 100 μM H2O2 per site.

[0075] Embodiment 12:

[0076] The infected wound of the rat was covered with the antibacterial dressing prepared in Comparative Example 3 and wrapped with a bandage for 12 hours before being discarded.

[0077] Embodiment 13:

[0078] The rats were treated with 100 μL of 100 μM H2O2 on the infected wound, and then covered with the antibacterial dressing prepared in Example 6 and irradiated with 1064 nm NIR laser for 10 min (0.75 W / cm 2 ) and then fix it with a bandage for 12 hours and discard.

[0079] Depend on Figure 7It can be seen that from the 0th day to the 9th day, the wound areas of the four groups were reduced to varying degrees, but the wound healing speed of Example 13 was the fastest. The difference in healing speed can be seen from the 3rd day. The wound healing rates of Examples 10 to 13 on the 3rd day were 7.60%, 38.4%, 25.0% and 41.3%, respectively. That is, on the 3rd day, the average wound healing rate of Example 13 was close to 50%, which was significantly higher than that of the other groups. Then from the 5th day, the 7th day to the 9th day, the average wound healing speed of Example 13 was basically the same as that of Example 11. This proves that Example 13 has the same effect on the body surface against Staphylococcus aureus wound infection, and can save the amount of iron-based polymer nanoparticles.

[0080] HE staining was performed on the skin tissue on the 9th day after surgery. Figure 8 As shown in the figure, a large amount of proliferating connective tissue and a large amount of lymphocytes, neutrophils and macrophages infiltration can be seen in the wound area of ​​Example 10, and there is epithelial erosion, while Example 11 has new skin tissue regeneration, accompanied by new skin appendages, such as hair follicles, but there are still some inflammatory cells. Although there is no epithelial erosion in Example 12, there is still a large amount of inflammatory cell infiltration. Example 13 shows that the epithelial tissue has recovered more regularly, indicating that the epidermis and dermis tissue are completely regenerated, and there are fewer inflammatory cells. It shows that Example 13 also has an excellent effect of promoting wound healing compared with Example 11.

[0081] The above is only a preferred embodiment of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a metal-based polymer nanoparticle antibacterial agent, characterized in that: The steps are: dissolving the polymer polypeptide in a polar solvent, adding a metal salt or an inorganic metal complex under stirring, heating to 25-160° C. for reaction for 2-24 hours, continuing the pyrolysis reaction after the reaction, the pyrolysis reaction temperature is 60-160° C., the time is 1-18 hours, and after the reaction, the product is collected, washed and dried to obtain a metal-based polymer nanoparticle antibacterial agent.

2. The method for preparing a metal-based polymer nanoparticle antibacterial agent according to claim 1, characterized in that: The obtained metal-based polymer nanoparticle antibacterial agent is modified with a modifying agent.

3. The method for preparing a metal-based polymer nanoparticle antibacterial agent according to claim 2, characterized in that: The modifier is triphenylphosphine.

4. The method for preparing a metal-based polymer nanoparticle antibacterial agent according to claim 3, characterized in that: The triphenylphosphine modifier is selected from one or more of the following: n-pentyltriphenylphosphonium bromide, methyltriphenylphosphonium bromide, ethyltriphenylphosphonium bromide, n-heptyltriphenylphosphonium bromide, benzyltriphenylphosphonium bromide or (3-carboxypropyl)triphenylphosphonium bromide.

5. The method for preparing a metal-based polymer nanoparticle antibacterial agent according to claim 3, characterized in that: When the modifier is triphenylphosphine, the steps are as follows: activating the triphenylphosphine modifier to obtain an activated triphenylphosphine solution, adding the activated triphenylphosphine solution dropwise into the metal-based polymer nanoparticle / water dispersion, stirring at room temperature in the dark for complete reaction, dialyzing the product solution to remove the raw materials that have not participated in the reaction, collecting the product, washing and drying to obtain the triphenylphosphine-modified metal-based polymer nanoparticles.

6. The method for preparing a metal-based polymer nanoparticle antibacterial agent according to claim 1, characterized in that: The polymer polypeptide is made of amino acids containing substituents, the amino acids are selected from one or more of the following: alanine, glutamic acid, glycine, leucine or valine, and the substituents are selected from one or more of the following: pyridyl, imidazole, carbazole, pyrrolyl or alkynyl; the polymer polypeptide contains a segment of a polyethylene glycol modifier, the polyethylene glycol modifier is selected from one or more of the following: methoxy polyethylene glycol amine, carboxyl polyethylene glycol amine or amino-terminated polyethylene glycol, and the molecular weight is 1000, 2000, 5000 or 10000; the degree of polymerization of the polymer polypeptide is 50 to 1000.

7. The method for preparing a metal-based polymer nanoparticle antibacterial agent according to claim 1, characterized in that: The metal salt is selected from one or more of the following: ferric chloride, ferrous chloride, ferric sulfate, ferrous sulfate, ferrous nitrate, ferrous carbonate or ammonium ferrous sulfate; the inorganic metal complex is selected from one or more of the following: Fe(CO)5, Co2(CO)8, Ni(CO)4, V(CO)6, Mo(CO)6, W(CO)6, Ru(CO)5 or Mn2(CO) 10 .

8. The method for preparing a metal-based polymer nanoparticle antibacterial agent according to claim 1, characterized in that: The polar solvent is selected from one or more of the following: dimethyl sulfoxide, N,N-dimethylformamide, acetone, dioxane, tetrahydrofuran, methyl ethyl ketone, methanol, n-butanol, ether, chloroform, N-methylpyrrolidone or o-dichlorobenzene.

9. The metal-based polymer nanoparticle antibacterial agent prepared by the method for preparing the metal-based polymer nanoparticle antibacterial agent according to claims 1 to 8, characterized in that: The particles are of a core-shell structure, wherein the core is a metal oxide particle and the shell is a polymer polypeptide.

10. The use of the metal-based polymer nanoparticle antibacterial agent as claimed in claim 9, characterized in that: 0.1-0.3 parts by weight of metal-based polymer nanoparticle antibacterial agent and 0-0.001 parts by weight of cationic antibacterial agent are added to 100 parts by weight of polyetherthiourea dressing precursor, and after mechanical stirring, the mixture is transferred to a mold to obtain an antibacterial dressing.

Citation Information

Patent Citations

  • Poly(peptide) as a chelator: methods of manufacture and uses

    CN101203249A

  • Polypeptide-zinc metal complex as well as preparation method and application thereof

    CN103667407A

  • Bifunctional gold @ polypeptide nanocomposite and preparation method and application thereof

    CN109530719A

  • Nutritional branched structure poly-polypeptide with efficient broad-spectrum antibacterial and fungal functions

    CN114989265A

  • Recyclable magnetic mesoporous antibacterial peptide nanoparticles constructed on basis of Fe-S bonds as well as preparation method and application of recyclable magnetic mesoporous antibacterial peptide nanoparticles

    CN115531516A